2002
DOI: 10.1016/s0735-1097(02)02304-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of valsartan on morbidity and mortality in patients with heart failure not receiving angiotensin-converting enzyme inhibitors

Abstract: Val-HeFT has provided the first placebo-controlled outcome data demonstrating a favorable effect of an angiotensin receptor blocker on mortality and morbidity in patients with HF not treated with ACE inhibitors. Based on these results, valsartan appears to be an effective therapy in ACE inhibitor-intolerant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(147 citation statements)
references
References 18 publications
7
125
0
15
Order By: Relevance
“…Despite increased utilization of pharmacological2, 3, 4, 5, 6, 7, 8, 9 and device therapy options10, 11, 12, 13 that improve clinical outcomes in randomized controlled trials, morbidity and mortality in HF remain a major burden to patients, their caregivers, and national healthcare systems. Patients with HF frequently experience worsening symptoms related to accumulation of excess intravascular volume and congestion, requiring hospitalization to provide intravenous medical support to restore normal volume 14, 15, 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increased utilization of pharmacological2, 3, 4, 5, 6, 7, 8, 9 and device therapy options10, 11, 12, 13 that improve clinical outcomes in randomized controlled trials, morbidity and mortality in HF remain a major burden to patients, their caregivers, and national healthcare systems. Patients with HF frequently experience worsening symptoms related to accumulation of excess intravascular volume and congestion, requiring hospitalization to provide intravenous medical support to restore normal volume 14, 15, 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…29 Evidence from ARB mega-trials Mega-trials of ARBs in patients with hypertension have confirmed that BP control with these agents reduces CVD morbidity and mortality in a range of patients, including those with diabetes mellitus, heart failure or LVH, and those at risk of developing heart failure following an MI. 31 In the double-blind, randomized Losartan Intervention for Endpoint Reduction in Hypertension (LIFE) study, more than 9000 patients with treated or untreated hypertension (mean baseline BP 174/98 mm Hg) and electrocardiographically documented LVH were assigned losartan-or atenolol-based therapy, with doses increased from 50 to 100 mg and other agents added, as necessary, to achieve a target BP of o140/90 mm Hg. 18 After a mean of almost 5 years of follow-up, BP fell by 30/17 mm Hg in the losartan group and 29/17 mm Hg in the atenolol group; at the Angiotensin II concentration Figure 1 Left ventricular mass in never-treated patients according to angiotensin II concentrations in relation to urinary sodium excretion.…”
Section: Reducing Cardiovascular Risk With Ras Inhibitors and Ccbsmentioning
confidence: 99%
“…18 One possible explanation for the subutilization of ACE inhibitors, which has been previously reported, is patient intolerance of the drug. 13,19 Although as many as 67% of HF patients discharged from hospitals are prescribed ACE inhibitors, 20 studies of outpatient visits report ACE inhibitor use of 39%, 21 and those of community-dwelling patients indicate ACE inhibitor use between 10% and 40%. 20,22 There is increasing evidence that ARBs can improve the clinical outcomes of patients with cardiovascular disease.…”
Section: Recommended Best Practicesmentioning
confidence: 99%
“…7,23 Valsartan, the only ARB with a U.S. Food and Drug Administration (FDA)-approved indication for HF patients, 7 is an alternative and effective therapy for patients who are intolerant of ACE inhibitors, according to the analysis of the subgroup of HF patients not receiving ACE inhibitors in the Val-HeFT. 13,19 More recently, candesartan demonstrated significant reductions in cardiovascular deaths and hospital admissions for HF in the CHARM trial, but it does not have an FDA-approved indication. 15 The Heart Failure Society of America (HFSA) recommends the use of ARBs when HF patients are intolerant of ACE inhibitors.…”
Section: Recommended Best Practicesmentioning
confidence: 99%
See 1 more Smart Citation